U f x applying the initial condition we discover that

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: e have 2y ) e y . u = f (x Applying the initial condition, we discover that f (x) = cos x, so the solution we seek is u (x, y ) = e y cos (x 2y ) . AMATH 350 9. 3y 2 ux Assignment #7 Solutions - Fall 2012 xuy = x, u(x, 0) = e x , y Page 9 0. We start by solving the equation dy = dx which is separable: 3 Z x , 3y 2 Z 2 y dy = xdx x2 + C. 2 Solving for C gives the characteristic curves: C = x2 + 2y 3 . We introduce a change of coordinates which will map these curves to straight horizontal (or vertical1 ) lines: Let ⇠ = x2 + 2y 3 , ⌘ = y. y3 = =) Then ux = and uy = @u @ u @⇠ ˆ @u ˆ = = 2x = 2x u⇠ ˆ @x @⇠ @ x @⇠ @u @ u @⇠ @ u @⌘ ˆ ˆ @u @u ˆ ˆ = + = 6y 2 + = 6 y 2 u ⇠ + u⌘ . ˆ ˆ @y @⇠ @ y @⌘ @ y @⇠ @⌘ These allow us to rewrite the given PDE: 3 y 2 ux x uy = x 3y 2 (2xu⇠ ) ˆ =) =) x 6 y 2 u⇠ + u⌘ = x ˆ ˆ u⌘ = ˆ 1. Now we can use partial integration: u= ˆ =) ⌘ + g (⇠ ) u= y + g x2 + 2 y 3 (You can easily verify that this solves the DE, for any differentiable function g ). All that remains is to apply the initial condition: u(x, 0) = e x2 =) e x2 = g x2 Therefore the solution to the given BVP is u(x, y ) = 1 =) g (x) = e x . 2 3 y + e (x +2y ) . The transformation ⇠ = x, ⌘ = x2 + 2y 3 works just as well....
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online